The 2021 Mw 7.3 East Cape Earthquake: Triggered Rupture in Complex Faulting Revealed by Multi‐Array Back‐Projections. Issue 20 (18th October 2022) - Xie, Y.; Meng, L.; Zhou, T.; Xu, L.; Bao, H.; Chu, R.
Abstract: On 04 March 2021 the Mw 7.3 East Cape, New Zealand earthquake occurred at the southern end of the Kermadec Trench. The United States Geological Survey W‐phase solution shows an unexpected focal mechanism compared to historical earthquakes. We combine earthquake back‐projections of 4 arrays to image the kinematic process of the Mw 7.3 earthquake. Our results reveal a bilateral rupture predominantly propagating upward at a slow speed of 1 km/s and a triggered rupture at ∼10 km, corresponding to the deep reverse faulting event at 70 km and a triggered shallow normal faulting event (∼20 km) resolved by previous subevent and finite fault inversions. The epicenter and a group of aftershocks are deeper than the bottom of the slab according to a regional tomography model. Such deep failure is possibly enabled by a delaminating lower crust of the Hikurangi plateau. Plain Language Summary: On 04 March 2021 the Mw 7.3 East Cape, New Zealand earthquake occurred at the southern end of the Kermadec Trench. Previous studies indicate that this earthquake ruptured multiple faults of different orientations. We apply a method using the recordings of 4 arrays of closely spaced sensors receiving earthquake signals to calculate the details of the earthquake source. Our results reveal that the rupture first propagates upward from 70 km at a slow speed of 1 km/s then a shallow rupture at ∼10 km is imaged. This result is consistent with the two subevents imaged by previous studies (Okuwaki et al., 2021, https://doi.org/10.1029/2021gl095117 ). The earthquake source and a group of aftershocks are in the mantle of the subducting Pacific plate, which is unusual because earthquake is prohibited due to high temperature and pressure. Such deep failure is possibly enabled by the sinking of part of the crust into the mantle. Key Points: We apply a multi‐array 3D back‐projection to image the rupture process of the 2021 Mw 7.3 East Cape earthquake Our results reveal a bilateral rupture predominantly propagating upward from 70 km and a triggered rupture at ∼10 km The deep rupture is in the mantle of the subducting Pacific plate, which is possibly related to a delaminating lower crust